2019
DOI: 10.5223/pghn.2019.22.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Treating Viral Diarrhea in Children by Probiotic and Zinc Supplements

Abstract: PurposeThe aim of this study was to analyze the effects of probiotics and zinc supplements on the mean duration and frequency of acute diarrhea in children aged 6 months to 2 years.MethodsIn this clinical trial of infants aged between 6 months and 2 years, eligible patients were divided into 3 groups: Zinc Receiving Group (ZRG), Probiotic Receiving Group (PRG), and a control group receiving supportive care alone. The frequency of diarrhea was evaluated in the test groups during the first 24 hours and 48–72 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…[ 2 , 17 ] The use of antidiarrheal drugs is not desirable for the improvement of such diarrhea symptoms, and it is known that probiotic formulations containing zinc, Lactobacillus species, and Saccharomyces species are helpful. [ 3 , 18 ] Even in our study, symptoms such as vomiting, fever, and abdominal pain did not last long. Maybe this explains why symptoms did not last long in any of the groups and why there was no difference between the 3 groups in terms of duration or severity.…”
Section: Discussioncontrasting
confidence: 63%
“…[ 2 , 17 ] The use of antidiarrheal drugs is not desirable for the improvement of such diarrhea symptoms, and it is known that probiotic formulations containing zinc, Lactobacillus species, and Saccharomyces species are helpful. [ 3 , 18 ] Even in our study, symptoms such as vomiting, fever, and abdominal pain did not last long. Maybe this explains why symptoms did not last long in any of the groups and why there was no difference between the 3 groups in terms of duration or severity.…”
Section: Discussioncontrasting
confidence: 63%
“…Epidemiologic studies have shown that factors that predispose children to diarrhoea are a complex interaction between socio-economic, environmental, and behavioural variables [14][15][16][17]. Diarrhoea-related morbidity and mortality among U5C have been linked to poor hygiene and sanitation practices [1,18], limited access to improved sources of drinking water [3,14], socioeconomic status, education level, place of residence [9], inappropriate breastfeeding [17,18], zinc deficiency [19] and other immediate household and environmental characteristics [5,8,14] The higher prevalence of diarrhoea in the LMIC has been attributed to the standard of living which differs across the rural-non-rural differences in place of residence [20].…”
Section: Introductionmentioning
confidence: 99%
“…The medical literature has shown discordance, referring to the role of zinc in the prevention and treatment of ADD in children. In a Cochrane study, conducted on 33 trials and 10,841 children, no favourable effects were found after zinc administration in the case of children suffering by ADD, but without zinc deficiency [43].On the other hand, Ahmadipour et al, in a study conducted in 2019 on 146 infants with V-ADD from Iran, sustain the positive effect of zinc administration on the duration, evolution and complications of the disease [44].…”
Section: Resultsmentioning
confidence: 97%